The implications of health sector reform for human resources development - Alwan Ala'; Hornby Peter (The World Health Organization, 2002)
The authors argue that "health for all" is not achievable in most countries without health sector reform that incorporates a process of coordinated health and human resources development. They examine the situation in countries in the Eastern Mediterranean Region of the World Health Organization. Though advances have been made, further progress is inhibited by the limited adaptation of traditional health service structures and processes in many of these countries. National reform strategies are needed. These require the active participation of health professional associations and academic training institutions as well as health service managers. The paper indicates some of the initiatives required and suggests that the starting point for many countries should be a rigorous appraisal of the current state of human resources development in health.